The Neogene-Quaternary diversification trend in the shaping of modern Caribbean mangroves. (15th January 2023) - Rull, Valentí
Abstract: This paper analyzes the diversification of the Neotropical mangrove flora from the Miocene to the present, using a fairly comprehensive database of 110 pollen records distributed across the whole Caribbean region. A Neogene-Quaternary diversification trend (NQDT) has been identified, characterized by an increase of 25 genera (∼78%) with respect to the 7 already existing Paleogene representatives. Only two genera appeared during the Miocene and the maximum increases were observed in the Pliocene-Quaternary transition and the modern-living record. Half of the true-mangrove genera ( Rhizophora, Pelliciera, Acrostichum ) were already present before the Neogene and the others appeared gradually in the Oligo-Miocene ( Crenea ), the Early-Middle Miocene ( Avicennia ) and the Mio-Pliocene ( Laguncularia ). None of the extant associate mangrove genera were present during the Paleogene and all appeared in the Miocene (23 genera) or the Oligo-Miocene transition (3 genera), being the main responsible for the NQDT, in absolute numbers. No regional extinctions were recorded since the Miocene in the Caribbean mangroves, at the generic level. These observations should be complemented with further high-resolution quantitative studies aimed at finding potential causal relationships with climatic, eustatic and paleogeographical shifts. Highlights: Metaanalysis of 110 Neogene to present Caribbean mangrove pollen records. ∼80% of the genera appeared during the Neogene-Quaternary diversification trend (NQDT). True mangrove elements (mangrove-forming trees) were already present in the Miocene. Associate mangrove genera were the main responsible for the NQDT. No extinctions (genera) and maximum diversification in the Pliocene-Quaternary transition.